Pelatihan Inovasi Teknologi Pembelajaran dalam Gerakan Literasi Digital di Masa Pandemi Pada SDN 01 Klegenserut - Ridho Pamungkas; Jeffry Handika; Reza Kusuma Setyansah; Lingga Nico Pradana (Politeknik Penerbangan Indonesia Curug, 2022)
Teachers and staff of the State Elementary School 01 Klegenserut, Jiwan District, Madiun Regency are required to be dynamic towards technological developments that are overgrowing so that their students can develop using available applications such as PowerPoint applications and Google Education. The use of the Microsoft PowerPoint application by using presentation slides and Google Education (Google Slides, Google Meet, and Google Drive) at the State Elementary School 01 Klegenserut, Jiwan District, Madiun Regency has not been optimal with the lack of ability of teachers and staff in presenting presentations using presentation media. This is from the Community Service Team providing training to these teachers and staff in addition to deepening the material for Microsoft PowerPoint and Google Education to provide skills in this application. This activity is carried out by preparing the material, ensuring the place and supporting facilities, explaining the theory about the material by direct practice, making student learning media and also this activity is carried out in the form of lectures, discussions, and questions and answers in the classroom which is attended by seven teachers and one teacher Administrative staff.